131k views
4 votes
Let f(x) = x − 3 and g(x) = x + 11.Find f(x) ⋅ g(x)

User Ellrohir
by
5.3k points

2 Answers

0 votes

Answer:
f(x).g(x)=x^2+8x-33.

Step-by-step explanation: We are given the following two functions ;


f(x)=x-3,~~~~~~~~g(x)=x+11.

We are to find the value of
f(x).g(x).

To find the required expression, we need to multiply the expressions for both the functions f(x) and g(x).

therefore, we get


f(x).g(x)\\\\=(x-3).(x+11)\\\\=x(x+11)-3(x+11)\\\\=x^2+11x-3x-33\\\\=x^2+8x-33.

Thus,
f(x).g(x)=x^2+8x-33.

User CindyH
by
4.8k points
1 vote

For this case we have the following functions:


f (x) = x-3\\g (x) = x + 11

We must find the product of the functions:


f (x) * g (x) = (x-3) (x + 11)

We apply distributive property, which states:


(a + b) (c + d) = ac + ad + bc + bd

So:


f (x) * g (x) = x ^ 2 + 11x-3x-33 = x ^ 2 + 8x-33

Answer:


x ^ 2 + 8x-33

User Martin Gamulin
by
5.2k points